Music Teachers’ Perspectives and Experiences of Ensemble and Learning Skills - Schiavio, Andrea; Küssner, Mats B.; Williamon, Aaron (Frontiers in Psychology, 2020)
In this article, we report data from two survey studies administrated to expert music teachers. Both questionnaires aimed to explore teachers’ pedagogical and performative practice and included open questions elucidating musical skills emerging in groups. The first study focuses on collective teaching settings involving amateurs, jazz musicians, and university students with various levels of expertise; the second reports data from educators based at the Royal College of Music, London, where the main emphasis is on classical repertoire as well as instrumental virtuosity and excellence. We integrate both studies and discuss overlapping findings in light of recent theoretical research in the cognitive sciences, which is increasingly applied to theory and practice in music education. We discuss suggestions for future research interested in teaching and learning music in different contexts and consider possible implications for educators interested in diverse skill levels.